Addition of all-trans-retinoic acid to omeprazole and sucralfate therapy improves the prognosis of gastric dysplasia. (April 2015) - Jin, Jianjun; Li, Xiaozhen; Xing, Luqi; Chang, Yongchao; Wu, Lijuan; Jin, Zhe; Su, Xiuli; Bai, Yanli; Zheng, Yufeng; Jiang, Yalin; Zhao, Xiao; Lu, Lan; et al.
Objective: To investigate the efficacy of all- trans retinoic acid (ATRA) in human gastric dysplasia. Methods: In this double-blind study, patients with precancerous gastric dysplasia with or without intestinal metaplasia (IM) received either conventional treatment consisting of omeprazole and sucralfate (control group) or conventional treatment plus ATRA. Gastric mucosal biopsies were performed before and after drug treatment and were analysed histologically; expression of retinoblastoma (Rb) protein and HER2 protein in gastric mucosa were measured using immunohistochemistry. Results: A total of 122 patients were included in the study, 63 in the ATRA group and 59 in the control group. In the ATRA group, dysplasia was attenuated in 43 out of 63 patients (68%) compared with 22 out of 59 patients (37%) in the control group; however, IM was not affected by treatment in either group. ATRA treatment was associated with significantly increased Rb expression and decreased HER2 expression in gastric mucosa. Conclusions: The use of conventional therapy plus ATRA for gastric dysplasia was associated with improved efficacy compared with conventional therapy alone. It was also accompanied by increased Rb expression and decreased HER2 expression in gastric mucosa. The addition of ATRA to conventional therapy for gastritis may improve the prognosis of gastric dysplasia.